2020
DOI: 10.21809/rilemtechlett.2020.112
|View full text |Cite
|
Sign up to set email alerts
|

Innovation potentials for construction materials with specific focus on the challenges in Africa

Abstract: Africa is urgently in need of adequate basic infrastructure and housing, and it is one of the continents where massive construction activities are on the rise. There is a vast variety of potentially viable resources for sustainable construction on the continents, and consequently, the continent can bring innovative, greener technologies based on local sources effectively into practice. However, unlike established concrete constituents from industrialised countries in the global North, most of the innovation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…By interrogating the urban futures built with concrete, it also questions the environmental impact of the construction industry in Africa, an issue that deserves deeper investigation (Van Damme 2018; Schmidt etal . 2020).…”
Section: Materials Matters In Urban Africamentioning
confidence: 99%
See 3 more Smart Citations
“…By interrogating the urban futures built with concrete, it also questions the environmental impact of the construction industry in Africa, an issue that deserves deeper investigation (Van Damme 2018; Schmidt etal . 2020).…”
Section: Materials Matters In Urban Africamentioning
confidence: 99%
“…2020; Schmidt etal . 2020). In France, the research centre CRAterre (International Centre for Earthen Architecture), based in Grenoble, is developing projects across the world with compressed earth block (CEB) technology, which is emerging as a potentially viable option in terms of price and sustainable objectives.…”
Section: Contesting Concrete Seeking Ecological Alternativesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that wood is the third consumption building materials next to cement and the world statistical review report stated that in 2015, the global cement produced was 4,6 billion tonnes and it is expected values between 6 and 13.5 billion tonnes in 2050 [21]. This is equivalent to about 626 kg/per capita, a value higher than the amount of human food consumption [17,22].…”
Section: Introductionmentioning
confidence: 99%